Winter's awakening - Gray, Shelley Shepard (New York : Avon Inspire, 2010)
"Shelley Shepard Gray returns with another heart-soaring saga of Amish life"--Publisher.
Keywords: Amish -- Fiction; Love stories; Christian fiction